Problems of Human Resources Fulfillment in Private Madrasah - Afif Kholidin; Ida Nur Lailatul Kodriyah; Andi Nurannisa Syam; Saifudin Zuhri; Muhamad Ali Abdul Basit (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Abstract Teacher human resources remains a primary challenge within the Indonesian educational landscape, particularly in private madrasahs where educators are frequently assigned to subjects that do not align with their academic backgrounds. This study aims to identify the structural and situational barriers to HR fulfillment and formulate strategic solutions to address this systemic mismatch. Designed as a qualitative multi-site case study, this research involves a comparative analysis across three educational levels (MI, MTs, and MA) in Demak Regency. Data were gathered through semi-structured interviews with principals and heads of curriculum, non-participant observations, and documentation analysis, followed by an interactive model analysis. The results indicate that HR fulfillment is primarily obstructed by a lack of financial equity in national budget distribution, high teacher turnover due to P3K recruitment, and a structural shortage of linear-background educators willing to work in the private sector. To address these issues, the study proposes the policy integration of PPPK into private institutions, the expansion of PPG opportunities, and the strengthening of collaborative networks with community organizations. The novelty of this research lies in its comprehensive focus specifically on human resource challenges within private madrasahs from various angles and factors, setting it apart from broader studies on educational problems. Keywords: cost of education, human resources, madrasah, quality of education, teacher professionality